Inventing a researcher’s culture in the semi-periphery, borderlands, and boundaries (not just disciplines) - Gołębniak, Marcin (Adult Education Discourses, 2024)
In my paper, I attempt to describe and interpret my own academic identity by focusing on my (auto)biographical and auto-ethnographic trajectory as a researcher and participant in academic culture, shaped at the boundaries of disciplines and academic institutions in a semi-peripheral country such as Poland. In the first part of the text, referring to Wallerstein’s concept of worlds-systems, I present the paradigmatic changes taking place in the discipline I practice – cultural anthropology – since the 1990s to the present day in conjunction with the pressures on the academia of non-English--speaking peripheral and semi-peripheral countries from English-speaking core countries, in order to reveal the biographical experience of the place of my own academic enculturation in a traditional university (ethnology at AMU), shaping the academic culture of which I am a user/bearer. In the following part of the paper, I analyse the relevance for the shift in my biography as a researcher and academic teacher of taking up a position in a specific academic environment and institution – in a Wrocław-based non-public university with academic aspirations (ULS) and the importance of the experience of being part of the research networks of the ESREA organization. In the final section of the essay, I focus on reconstructing how educational work with so-called non-traditional students, focused on their undertaking explorations within their own culture through various techniques of the ethnographic method, redefines my research and teaching practices and shapes my current academic identity.